Does Parental Income and Education Improve Academic Achievement?: A Case of Public High School Students at Tangerang Municipality - Sentosa, Bambang Mardi (FKIP Universitas Lampung, 2023)
Objectives: The study aims to examine the relationship between parents' socioeconomic status and the academic achievement of public high school students in Tangerang Municipality. Methods: This research is a cross-sectional study of 660 (Cochran formulation with a sampling error of 3.7%) students from a total of 6,551 public senior high schools.. The author utilized a random sampling technique. The primary data was obtained through a questionnaire that has been tested for validity and reliability. The questionnaires were distributed to the participants using the students' WhatsApp groups. The author used a binary logit regression model for data analysis. Findings: The results showed that socioeconomic status significantly impacted on student academic achievement. Parents of students with high socioeconomic status were more likely to improve their child's academic results. Meanwhile, the composition of parents' socioeconomic status that contributes more dominantly to increasing academic achievement is the father's income and education and the mother's education, but not the mother's income and asset. Conclusion: Thus, one of the determinants of the academic achievement of high school students is the socioeconomic condition of their parents. The results of this study provide not only an expansion of the education science and education economics literature but also empirical implications for parents and secondary education policymakers. Keywords: academic achievement, assets, parental income, education.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202318